The analysis of BOD (Biological Oxygen Demand) and COD (Chemical Oxygen Demand) contents in the water of around laying chicken farm. Issue 1 (June 2021) - Abdullahi, A B; Siregar, A R; Pakiding, W; Mahyuddin,
Abstract: Business activities of laying chicken farm in Sidrap regency have been carried out for decades. This business is a hereditary business carried out by the local community. The number of chicken populations is also increasing as the demand for animal protein increases. This activity can lead to a decrease in water quality, thereby affecting the environmental sanitation system. Clean water is needed in meeting human needs to carry out all their activities. Based on this, an environmental test was carried out by analyzing the BOD and COD contents of water around laying chicken farms. This research aims to (1) determine the BOD and COD contents of water around the laying chicken farm, (2) comparing the BOD and COD contents of water around the laying chicken farm with the threshold value set by the government. This research was conducted in October - December 2018 in Sidenreng Rappang regency, South Sulawesi Indonesia. The method used in the water BOD content test is the Winkler method, while for water COD is the spectrophotometric method. The results show that the BOD contents of water around the laying chicken farm was 7.99 mg/L on average, and the water COD content was 18.47 mg/L. This research concluded that the BOD and COD contents of water around the laying chicken farm exceeds the threshold set by the government. The threshold for water BOD content is 2 mg/L while for water COD is 10 mg/L.